PENGEMBANGAN COMMUNITY BASED TOURISM (PARIWISATA BERBASIS MASYARAKAT) DI DESA WISATA SAMIRAN BOYOLALI - Riyandi, Angga Novi; Martini, rina - (Journal of Politic and Government Studies, 2024)
This research was conducted in order to find out what form of community-based tourism management exists in the Samiran Boyolali Tourism Village, where Community Based Tourism which focuses on community empowerment is an interesting topic to discuss in the world of village government. This research is a qualitative research with the subject of the Guyub Rukun Tourism Awareness Group (Pokdarwis) of the Samiran Tourism Village, the Samiran Village Government, and the Boyolali Regency Youth Sports and Tourism Service using interview, observation and documentation study data collection techniques. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The research results reveal that tourism management in the Samiran Tourism Village using the Community Based Tourism concept is carried out by considering 5 principles, namely community economic growth, social, preservation of local culture, environmental conservation, and community participation in tourism development through Pokdarwis. The Department of Youth, Sports and Tourism together with Pokdarwis in this research play a role in encouraging public awareness of tourism potential, improving the quality of local community human resources, providing direction and responsibility to the community to manage tourism directly. In terms of Good Governance, the Boyolali Regency Government has an important role in developing tourism in the Samiran Tourism Village, namely as a party that provides moral support to the village community, provides facilities that are able to support tourism development, and finally as a liaison between stakeholders in working together for village development Samiran Tourism